2022
DOI: 10.5603/rpor.a2022.0108
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionation as a solution to radiotherapy access in latin america: expert perspective

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Low rates of acute toxicity were observed in this study, No grade ≥ 3 acute toxicity were observed, are consistent with the findings of other studies that have evaluated hypofractionation schedules for prostate cancer (17,18,19,20), and the incidence rates of Grade ≥2 acute GU y GI toxicities pág. 7022…”
Section: Discussionsupporting
confidence: 92%
“…Low rates of acute toxicity were observed in this study, No grade ≥ 3 acute toxicity were observed, are consistent with the findings of other studies that have evaluated hypofractionation schedules for prostate cancer (17,18,19,20), and the incidence rates of Grade ≥2 acute GU y GI toxicities pág. 7022…”
Section: Discussionsupporting
confidence: 92%
“…This study allows us to evaluate the safety profile of hypofractionated schemes in postoperative prostate cancer and the feasibility of including elective treatment of the pelvis, which is in line with what is recommended by area experts in the region [35]. However, this protocol has some limitations.…”
Section: Discussionmentioning
confidence: 72%
“…Hypofractionated RT (HRT) has emerged as a viable solution for tackling the scarcity of RT, particularly in LMICS. HRT involves administering a higher radiation dose with each session (fraction) using either moderate (>2-4 Gy per fraction) or ultra-hypofractionation (>5 Gy per fraction) [14], thereby reducing the overall duration of RT [10,15,16]. From a radiobiological standpoint, hypofractionation offers many therapeutic benefits, especially for tumors characterized by low α/β ratios [17].…”
Section: Introductionmentioning
confidence: 99%